Improvement of Students' High Order Thinking Skills (HOTS) Ability through the Application of Van Hiele Theory Assisted by Video Animation - Kairuddin, Kairuddin; Siregar, Budi Halomoan; Siregar, Nur Hasanah (Journal of Mathematical Pedagogy (JoMP), 2020)
Geometry, which is a branch of mathematics related to visualization often makes students less motivated. Thus, the ability to think mathematically, which is suitable with Van Hiele's geometric thinking ability, need to be promoted in any interactive mathematics learning. Thus, this research is aimed at examining how students' high order thinking skills through the application of Van Hiele's theory with the help of animated videos.  Van Hiele's geometric thinking stages consist of visualization, analysis, abstraction, deduction, and rigor. To apply it, researchers used the Thiagarajan learning model known as the Four-D Model. Participants involved in this study were eleventh grade students of an Islamic secondary school in Sumatra, Indonesia. The instruments used were learning tests and student worksheets. Results indicates that Van Hiele's theory aided by video animation helps students improve students thinking skills and students experience regarding their ability to solve geometric higher-order thinking skill problems.Keywords: HOTS, Van Hiele, Geometry, Video Animation